2016
DOI: 10.1097/mnm.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of total lesion glycolysis measured by 18F-FDG PET/CT in patients with locally advanced cervical cancer

Abstract: Pretreatment TLG proved to be an independent prognostic factor for RFS in patients with locally advanced cervical cancer treated by definitive chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
5
22
0
Order By: Relevance
“…In our study, SUVmax and SUVmean had no signi cant in uence on OS, DFS, LC or DMFS. There are several articles with similar results to our study [13,21]. SUV may be affected by many factors, such as body mass index, blood glucose level, scan duration, and reconstruction algorithm [22][23][24].…”
Section: Discussionsupporting
confidence: 79%
“…In our study, SUVmax and SUVmean had no signi cant in uence on OS, DFS, LC or DMFS. There are several articles with similar results to our study [13,21]. SUV may be affected by many factors, such as body mass index, blood glucose level, scan duration, and reconstruction algorithm [22][23][24].…”
Section: Discussionsupporting
confidence: 79%
“…Kidd et al found that SUVmax of the primary tumor also has other prognostic value, having a correlation with histology and differentiation[11]. Other quantitative data obtained from PET/CT have been shown to be helpful, such as metabolic tumor volume (MTV) and total lesion glycolysis (TLG) [12, 13]. Zhang et al compared the gross tumor volume (GTV) as assessed by CT, MRI, and PET/CT to pathologic volume in 10 patients with stages I-II cervical cancer, and found that PET/CT GTV determined under 40% SUVmax had the best correlation with pathology volume [14].…”
Section: Stagingmentioning
confidence: 99%
“…Most of those prognostic factors are derived from inherent characteristics of the tumor including tumor size, FIGO stage and lymph node involvement. [1][2][3] Additionally, various tumor metabolic parameters derived from 18F-FDG PET, including maximum standardized uptake value (SUVmax), 4 metabolic tumor volume (MTV), 5 total lesion glycolysis (TLG) 6 and more recently, radiomic features, 7 have been shown to be accurate and sensitive prognostic biomarkers. Some treatment features, such as the volume of the high-risk clinical target volume (HR-CTV) or the dose received by 90% of the HR-CTV, 8 have also demonstrated potential in predicting local control.…”
Section: Introductionmentioning
confidence: 99%